Genome-wide characterization of i-motifs and their potential roles in the stability and evolution of transposable elements in rice. Issue 6 (21st February 2022) - Ma, Xing; Feng, Yilong; Yang, Ying; Li, Xin; Shi, Yining; Tao, Shentong; Cheng, Xuejiao; Huang, Jian; Wang, Xiu-e; Chen, Caiyan; Monchaud, David; Zhang, Wenli
Abstract: I-motifs (iMs) are non-canonical DNA secondary structures that fold from cytosine (C)-rich genomic DNA regions termed putative i-motif forming sequences (PiMFSs). The structure of iMs is stabilized by hemiprotonated C-C base pairs, and their functions are now suspected in key cellular processes in human cells such as genome stability and regulation of gene transcription. In plants, their biological relevance is still largely unknown. Here, we characterized PiMFSs with high potential for i-motif formation in the rice genome by developing and applying a protocol hinging on an iMab antibody-based immunoprecipitation (IP) coupled with high-throughput sequencing (seq), consequently termed iM-IP-seq. We found that PiMFSs had intrinsic subgenomic distributions, cis -regulatory functions and an intricate relationship with DNA methylation. We indeed found that the coordination of PiMFSs with DNA methylation may affect dynamics of transposable elements (TEs) among different cultivated Oryza subpopulations or during evolution of wild rice species. Collectively, our study provides first and unique insights into the biology of iMs in plants, with potential applications in plant biotechnology for improving important agronomic rice traits.